1993
DOI: 10.1037/0003-066x.48.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Development during adolescence: The impact of stage-environment fit on young adolescents' experiences in schools and in families.

Abstract: Although most individuals pass through adolescence without excessively high levels of "storm and stress," many do experience difficulty. Why? Is there something unique about this developmental period that puts adolescents at risk for difficulty? This article focuses on this question and advances the hypothesis that some of the negative psychological changes associated with adolescent development result from a mismatch between the needs of developing adolescents and the opportunities afforded them by their soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

129
2,092
16
79

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,456 publications
(2,316 citation statements)
references
References 43 publications
129
2,092
16
79
Order By: Relevance
“…Higher levels of anxiety disorders and somatization symptoms have been consistently documented among Hispanic adults, and it is likely that increases in these symptoms in this group first occurs during adolescence. Early adolescence is associated with a number of social and biological stressors (e.g., Eccles et al 1993) that, paired with increased conflict between traditional and mainstream cultural values, may place Hispanic adolescents, particularly females, at higher risk for developing anxiety symptomatology during this period. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of anxiety disorders and somatization symptoms have been consistently documented among Hispanic adults, and it is likely that increases in these symptoms in this group first occurs during adolescence. Early adolescence is associated with a number of social and biological stressors (e.g., Eccles et al 1993) that, paired with increased conflict between traditional and mainstream cultural values, may place Hispanic adolescents, particularly females, at higher risk for developing anxiety symptomatology during this period. …”
mentioning
confidence: 99%
“…Early adolescence represents a particularly important age group in which to make such comparisons. The transition to middle school or junior high is well-documented to be a trigger for the emergence of psychopathology and maladjustment (Eccles et al 1993;Robinson et al 1995;Seidman et al 1994) given the many academic and social stressors and biological changes that occur during this time period. Moreover, an increase in rates of major depression in females is consistently documented to occur between the ages of 13 and 15 (see Twenge and Nolen-Hoeksema 2002), and the gender difference in depression is first observable during this period (Hankin et al 1998).…”
mentioning
confidence: 99%
“…Većina istraživanja u domenu motivacionih aspekata uspjeha ukazuje da postoje značajne promjene u motivaciji za učenje prilikom prelaska iz rane u srednju adolescenciju. Stariji adolescenti imaju nižu motivaciju za školske sadržaje i slabiji uspjeh što može biti objašnjeno razvojno-dinamičkim procesima [5]. Каdа је riječ о polnim razlikama u ispoljenosti mоtivacije zа školsko učenje, dosadašnji istraživački nalazi nisu kоnzistentni [6].…”
Section: Diskusijaunclassified
“…Opadanje školskog uspjeha sa uzrasom moguće je pripisati manjem zalaganju i opadanju motivacije za postignućem kod starijih učenika [5]. Van Wersch i sar.…”
Section: Diskusijaunclassified
“…The authors suggested that it was unclear why this "wave-like pattern" of the magnitude of the effect size occurred across ages. Some additional evidence suggests that the age range between 9 and 12 has been linked to a number of variables including decreases in parental monitoring and increases in the hostility of the school environment, child autonomy within the school environment, and peer influence on children (Blyth et al, 1978;Eccles et al, 1993;Fite et al, 2006). Research has indicated that the role of peer influence on children also shows a curvilinear pattern in which children's conformity with their peers peaks during the middle-school years (Berndt, 1979 (Leff et al, 2006;Lochman & Dodge, 1994;Weiss, Dodge, Bates, & Pettit, 1992).…”
Section: Reactive Vs Proactive Aggressionmentioning
confidence: 99%